2005
DOI: 10.1007/s11104-004-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the dielectric permittivity of a plant canopy and its response to changes in plant water status: An application of Impulse Time Domain Transmission

Abstract: Impulse Time Domain Transmission (ITDT) has been used to measure the complex dielectric permittivity of media such as ethanol, water and variably saturated sand. This paper applies ITDT to measurements of the complex dielectric permittivity of a vegetation canopy. The dielectric permittivity of a vegetation canopy is very close to that of air and only very small changes in its value will occur with changes in plant water status. This paper presents preliminary results demonstrating that ITDT can make repeatabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…5, the oven-dry experiments showed that the intrinsic water of organics, for example, the leaves or watermelon peel, accounts for 95 percent of the total mass of organics. The K a of a plant is a mixture of free water, bound water, and plant dry matter (Burke et al, 2005). Therefore, before being mixed with any water, the K a of leaves or watermelon peel is much higher than paper and plastic.…”
Section: Resultsmentioning
confidence: 99%
“…5, the oven-dry experiments showed that the intrinsic water of organics, for example, the leaves or watermelon peel, accounts for 95 percent of the total mass of organics. The K a of a plant is a mixture of free water, bound water, and plant dry matter (Burke et al, 2005). Therefore, before being mixed with any water, the K a of leaves or watermelon peel is much higher than paper and plastic.…”
Section: Resultsmentioning
confidence: 99%
“…Since the only variation in the plant system throughout time is loss of water due to evaporation and that our measurement technique is especially sensitive to water (due to its high dielectric constant), we can assume that the variations in light/dark electrical parameters are due to losing water. The effects of water loss on electrical properties are a well-known effect [34] As discussed in the introduction, admittance signals can also be represented in the form of a vector on a complex plane in order to facilitate its analysis. It is formed by two components, Y G jB = + : susceptance ( B C ω = ) and conductance ( 1 G R =…”
Section: Resultsmentioning
confidence: 99%
“…• He et al developed a portable bioelectrical impedance spectroscopy system able to detect tomato plant water status [30]. • Burke et al showed that Impulse Time Domain Transmission (an extension of Time Domain Reflectometry, an electromagnetic technique used for measuring the dielectric constant of soils, which is related to soil water content) is very sensitive to small changes in plant canopy water status [34].…”
Section: Introductionmentioning
confidence: 99%
“…After application of water to the trees, both water potential and dielectric constant in the xylem increased. Burke et al (2005) used lab measurements of leaf dielectric constants to show the relation between relative water content and the dielectric constant. Dobson et al (1991) found that dielectric constant of loblolly pine trunks were partially correlated to canopy layer physiological observations, such as transpiration, stomatal conductance and xylem water potential.…”
Section: Relation Between Plant Dynamics and Dielectric Prop-ertiesmentioning
confidence: 99%